Proceedings of the XTH International Scientific Congress in Fur Animal Production 2012
DOI: 10.3920/978-90-8686-760-8_77
|View full text |Cite
|
Sign up to set email alerts
|

Aleutian mink disease virus in furbearing mammals in Nova Scotia, Canada

Abstract: Background: Aleutian mink disease virus (AMDV) is widespread among ranched and free-ranging American mink in Canada, but there is no information on its prevalence in other wild animal species. This paper describes the prevalence of AMDV of 12 furbearing species in Nova Scotia (NS), Canada. Methods: Samples were collected from carcasses of 462 wild animals of 12 furbearing species, trapped in 10 NS counties between November 2009 and February 2011. Viral DNA was tested by PCR using two primer pairs, and anti-vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
28
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 13 publications
(22 reference statements)
1
28
1
2
Order By: Relevance
“…The disease occurs in wild and domesticated mink (Bloom et al 1994;Nituch et al 2011Nituch et al , 2012, and has been reported in many jurisdictions where domestic mink are raised; it is apparent that the commercial trade of domestic mink contributes to the spread of the virus (Bloom et al 1994;Nituch et al 2012). Aleutian mink disease virus can be highly prevalent in wild mink populations (Nituch et al 2011;Farid 2013) and mink farms can be point sources of disease (Nituch et al 2011), but the extent to which wild and domestic mink transmit AMDV, and other wildlife act as reservoirs, is unknown (Nituch et al 2012;Farid 2013). …”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The disease occurs in wild and domesticated mink (Bloom et al 1994;Nituch et al 2011Nituch et al , 2012, and has been reported in many jurisdictions where domestic mink are raised; it is apparent that the commercial trade of domestic mink contributes to the spread of the virus (Bloom et al 1994;Nituch et al 2012). Aleutian mink disease virus can be highly prevalent in wild mink populations (Nituch et al 2011;Farid 2013) and mink farms can be point sources of disease (Nituch et al 2011), but the extent to which wild and domestic mink transmit AMDV, and other wildlife act as reservoirs, is unknown (Nituch et al 2012;Farid 2013). …”
mentioning
confidence: 99%
“…Wildlife other than American mink can become infected with or exposed to AMDV, including striped skunk (Mephitis mephitis), ermine (Mustela erminea), European mink (Mustela lutreola), raccoon dog (Nyctereutes procyonoides), and raccoon (Procyon lotor) (Alexandersen et al 1985;Mañ as et al 2001;Pennick et al 2007;Farid 2013). Given demonstrated global problems with mink farm biosecurity (Bonesi and Palazon 2007;Bowman et al 2007), there is potential for mink farms to be sources of cross-species spillover of AMDV (Nituch et al 2011(Nituch et al , 2012.…”
mentioning
confidence: 99%
See 3 more Smart Citations